AN OCB on Employee with Job Satisfaction as Mediator of Leadership and Organizational Climate - Histayanthi, Kadek Dwi; Puspitawati, Ni Made Dwi; Tahu, Gregorius Paulus; Prastyadewi, Made Ika (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2024)
Organizational Citizenship Behavior is essential for companies because it encourages a collaborative and supportive work environment, improves teamwork, and improves employee morale by enabling employees to look beyond their formal job descriptions. This study aims to analyze OCB in employees with job satisfaction as a mediator of leadership and organizational climate. This exploratory study uses a quantitative descriptive method based on a pattern of relationships that describes the causal relationship between variables. The population in this study was all 53 employees. The sampling technique used was non-probability sampling with a saturated sampling technique. Data collection method with a questionnaire. Data collection instruments with questionnaire sheets. Data analysis techniques with inferential statistics. The study's results indicate that leadership, organizational climate, and job satisfaction affect OCB, and job satisfaction can mediate the influence of leadership and OCB. OCB leads to better productivity, improved customer service, and a positive organizational culture. This proactive behavior encourages organizational flexibility, reduces employee turnover and operating costs, and strengthens the company's reputation. Ultimately, OCB impacts the company's success and sustainability by creating a more engaged and motivated workforce.